Issues and challenges in cataloguing arabic books in Malaysian academic libraries / Mohd Ikhwan Ismail and Nurul Azurah Md. Roni - Ismail, Mohd Ikhwan; Md Roni, Nurul Azurah (2011)
Education in Library and Information Science is a requirement to become a librarian. There are a lot of syllabuses and subjects to concentrate on such as cataloguing and classification, information retrieval, knowledge management, and reference. Library as a centre of information has been developing year by year with various types of collections written and presented in many languages such as English, Arabic and Malay. The different languages come with different letters, words, pronunciations and characters. They can bring problems and challenges in cataloguing process including determining the access points, subject headings and call number. The objective of this study is to identify the challenges in cataloguing Arabic books for cataloguers in Malaysian academic libraries. This study aims to investigate the relationships and differences between Arabic and Roman scripts in cataloguing process. The comparison is made to discover the similarities and differences in the problems faced by cataloguers from different academic libraries in Klang Valley namely International Islamic University Malaysia (IIUM), University of Malaya (UM), National University of Malaysia (UKM), Islamic Science University of Malaysia (USIM) and International Islamic University College Selangor (KUIS). The method used in data collection in this study is personal interview with cataloguers responsible for cataloguing Arabic books. The findings show that the major problem is in the Arabic scripts. They are difficult to vocalize Arabic words due to the different ways of reading the various types of calligraphy and typography. Besides, the issues of lengthy author‘s name, vocalization of name and Arabization of English name also create problems to the cataloguers. Some of the integrated library systems cannot adopt the Arabic characters. Another problem is the difficulty to determine the subject heading for Arabic books that are not accurately stated in the Library of Congress Subject Heading (LCSH) besides the unavailability of new Arabic terms. However, the cataloguing process of Arabic books is still on-going even though there are a lot of problems that come out without solutions. Although transliteration can be one of the solutions, it is still not the best one. This study will help to improve the Library and Information Science education to cope and face the challenges in library work field.